Training Based on the Andragogy Approach to Improve the Ability to Develop Independent Learning Modules for Vocational School Teachers - Hirnanda Dimas Pradana; Andi Kristanto; Irena Yolanita Maureen (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to improve the ability of teachers to arrange learning modules. This program was carried out through in-service training (IST) and on-service training (OST) methods. The andragogy approach was used in IST activities to improve teachers' ability to analyze learning materials that can be the basis for learning modules. Thirty Vocational High School Teachers attended this activity. The evaluation used was to give project assignments to the teacher for module work. The training participants were also given a Google form to fill out. The analysis used was descriptive quantitative. The results of the OST showed that the teacher had been able to analyze learning problems; the teacher understood the concept of the learning module. Moreover, the teacher could understand the idea of preparing a learning module, and the concept of evaluating the learning module. A series of OST activities conclude that teachers have the potential to develop themselves in preparing learning modules; the resulting learning modules can be categorized as good and, in general, have met the criteria for learning modules.